(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of a rational-emotional-behavioral counseling program on developing situational support among female boarding students. The researcher used a quasi-experimental design, constructing a situational support scale consisting of (24) items. The application sample was intentionally selected from female boarding students, comprising (10) students for the experimental and control groups. The researcher then designed a cognitive-behavioral counseling program based on the "S" theory to develop situational support according to the Borders and Drury model. The researcher used a statistical package to analyze the data. The researcher concluded that the rational-emotional-behavioral counseling program is effective in developing situational support, as shown by the results, which showed that there are statistically significant differences between the average scores of female students in the experimental and control groups on the situational support scale in the pre- and post-tests. In light of the results of the current research, the researcher came up with a set of recommendations and proposals.